Efusión Pericárdica En Un Cobayo (Cavia Porcellus). Reporte De Un Caso Clínico Durante La Pasantía Realizada En Una Clínica Veterinaria En Bogotá. (2023)
The following internship report describes the clinical case of a three-year-old guinea pig that presented to veterinary care because it had respiratory distress. Clinical examination revealed cyanotic lingual mucosa and lips, abdominal distension, pain on palpation, barely audible heart sounds, open-mouthed breathing, and thoracic auscultation with deaf foci.